Synthesis and Characterization of Maleic Anhydride Modified Poly (Ethylene Glycol) as Polymeric Solid-Solid Phase Change Materials - Tuğba Güngör Ertuğral; Cemil Alkan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, a novel type of polymeric solid-solid phase change materials (SSPCMs) and Maleic anhydride (MA) modified poly (ethylene glycol) PEG. MAM-PEG polymers were synthesized from different moleculer weight PEG (Mw: 4000, 6000) .On the other hand two different catalyst system was used; para toluene sulfonic acid (PTSA) and 1,8-Diazabicyclo [5.4.0] undec-7-ene (DBU).The PEG bound to the backbone of the polymers formed crystalline regions responsible from latent heat storage with reversible crystalline to amorphous phase transition as linked unit prevented total melting of the structure. Also MAM-PEG polyester polymers acid and hydroxyl values were determined for number of average molecular weight (Mn) and calculated as 36232 and 49020. Characterization and thermal properties of SSPCMs were performed by using fourier transform infrared (FT-IR) spectroscopy and differential scanning calorimetry (DSC) techniques mainly. DSC results showed that solid-solid transitions 36-54 °C temperature range and 163-153 Jg-1 enthalpy. As a result, MAM-PEG polymers were found potential for thermal energy storage (TES) applications.